Participatory Action Research : The Persistence of Utopias - Banguero Velasco, Rigoberto; Gruber, Valerie (2021)
To stimulate social change beyond the academic field, Participatory Action Research (PAR) integrates local communities into a collaborative knowledge production. This emancipatory research methodology developed by Colombian sociologist Orlando Fals Borda and other Latin American thinkers aims at minimizing power hierarchies between the researchers and the researched, while overcoming rigid distinctions between theory, methodology and practice. During the workshop, we will share hands-on experience in adopting the PAR approach with Afro-descendant and indigenous communities in Colombia, and discuss its applicability in Africa and beyond. In an interactive setting, we will address the following questions: Why is the subject-object relation problematic in PAR? How is knowledge produced in PAR (under which conditions and in which contexts)? How can we promote a dialogue of academic and popular knowledges? What are the differences between PAR and militant research? What are the gnoseological bases of PAR? Which strategies are used to carry out a systematic return of knowledge to the communities? We will also discuss how to ensure that the committed research process meets academic quality requirements of reflexive knowledge production. In this way, the participants will gain theoretical and practical skills enabling them to apply the PAR approach in their own research projects.